KNOWLEDGE ATTITUDE AND PERCEPTION OF HYPERTENSION AMONG STAFF OF A TERTIARY INSTITUTION IN NIGERIA - AA, Mgbahurike; TN, Lelesi (Universal Journal of Pharmaceutical Research, 2022)
Background: Hypertension was a prevalent disease in developed countries, but has recently become a major disease of public health importance in developing countries. Objective: Study assessed knowledge, attitude, and perception about hypertension among the staff of University of Port Harcourt, Rivers State. Method: Cross- sectional study was conducted among the staff in July 2019. 256 staff was randomly selected across all the Faculties. Data collected using structured questionnaire include, demographic information, knowledge, perception and attitude about hypertension and statistical analysis carried out with SPSS version 20 Result: Total 54.7% (140) respondents were academic staff and 45.3% (116) non- academic. 61.7% (158) male, females constitute 38.3% (98). Male academic staff was 67.1% (94); most academic staff, 36.4% (51) was within 50-59 years, 28.6% (40) were between 40-49 years. Total 37.1% (43) non-academic staff were within 40-49yrs. Respondents have a good knowledge, 87.9%, of hypertension, but only 61% (85) of academic and 47% (54) non-academic staff knew that hypertension can be inherited. Total 40% (56) academic, 44.8% (52) non-academic claimed to have multiple source of information about hypertension. Knowledge on risk factors of hypertension was poor, 20%. Conclusion: Knowledge level of respondents on hypertension was high, with moderate attitude but poor perception. Peer Review History: Received: 3 December 2021; Revised: 6 January 2022; Accepted: 8 February, Available online: 15 March 2022 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewers: Md. Monirul Islam, Department of Pharmacy, Faculty of Health Sciences, Northern University Bangladesh, Dhaka, Bangladesh. monirul.islam@nub.ac.bd Rola Jadallah, Arab American University, Palestine, rola@aauj.edu